(untitled) (International Conference on Computers in Education, 2022)
This study reports the findings of a qualitative case study on the role of embodiment and gesture in immersive virtual reality (IVR)-enhanced Natural Sciences (NS) learning. 32 NS pre-service teachers (PSTs) participated in the study, and qualitative data were gathered through observations and follow-up focus group semi-structured interviews. From a content analysis of observations and interviews, the following assertions were arrived at: Gesture and manipulation of virtual objects enhance spatial reasoning while fostering experiential and authentic learning experiences: Both bodily (physical) and virtual manipulations in IVR-enhanced learning have a positive effect on cognitive processes, and lastly that the combination of audio, visual and embodied actions together have a higher impact of long-term memory and retention of NS concepts. Some implications and future directions are also discussed in this paper